Synonymous Mutations in RNASEH2A Create Cryptic Splice Sites Impairing RNase H2 Enzyme Function in Aicardi–Goutières Syndrome. Issue 8 (13th May 2013) - Rice, Gillian I.; Reijns, Martin A.M.; Coffin, Stephanie R.; Forte, Gabriella M.A.; Anderson, Beverley H.; Szynkiewicz, Marcin; Gornall, Hannah; Gent, David; Leitch, Andrea; Botella, Maria P.; Fazzi, Elisa; Gener, Blanca; et al.
<x xml:space="preserve">Abstract</x> Aicardi‐Goutières syndrome (AGS) is an inflammatory disorder resulting from mutations in TREX1, RNASEH2A/2B/2C, SAMHD1 or ADAR1. In this study, we provide molecular, biochemical, and cellular evidence for the pathogenicity of two synonymous variants in RNASEH2A, resulting in a loss of RNase H2 enzyme activity and the consequent AGS phenotype. In our cohort of 265 AGS pedigrees, four of thirteen families with RNASEH2A mutations harbor one of the two splicing variants described here. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>